2010
DOI: 10.1007/s13353-010-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

FISH in analysis of gamma ray-induced micronuclei formation in barley

Abstract: A micronucleus test in combination with fluorescent in situ hybridization (FISH) using telomere-, centromere-specific probes and 5S and 25S rDNA was used for a detailed analysis of the effects of gamma ray irradiation on the root tip meristem cells of barley, Hordeum vulgare (2n = 14). FISH with four DNA probes was used to examine the involvement of specific chromosomes or chromosome fragments in gamma ray-induced micronuclei formation and then to explain their origin. Additionally, a comparison of the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…These observations indicate that despite their similar size, Bd4 chromosomes are involved in the MH-induced micronuclei formation more often than Bd5 chromosomes. Similar results were observed in gamma ray-induced micronuclei in barley [4]. Moreover, an additional locus of 35S rDNA was present after MH treatment in barley cells, which suggests that either a duplication or double strand breaks (DBS) occurred within the 35S rDNA locus.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…These observations indicate that despite their similar size, Bd4 chromosomes are involved in the MH-induced micronuclei formation more often than Bd5 chromosomes. Similar results were observed in gamma ray-induced micronuclei in barley [4]. Moreover, an additional locus of 35S rDNA was present after MH treatment in barley cells, which suggests that either a duplication or double strand breaks (DBS) occurred within the 35S rDNA locus.…”
Section: Resultssupporting
confidence: 81%
“…Our data correspond to that reported by Jovtchev et al [1], who showed that only 1% of MNU-induced barley micronuclei revealed centromere DNA signals. Interestingly, the frequency of such micronuclei in barley that was subjected to MH treatment was considerably higher (6%) [5], whereas they were not observed at all in barley cells after gamma radiation [4]. Such discrepancies in the frequencies may indicate that only MH and MNU cause interstitial chromosome breaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variable micronuclei compositions also are observed in barley (Hordeum vulgare) root cells to analyze the effects of Gamma ray irradiation. 67 Furthermore, the presence of 18S rDNA in micronuclei of tamoatás may result in problems in the production of ribosomes, which are responsible for protein synthesis, since the 18S rDNA was shown to be active in micronuclei when subjected to impregnation with silver nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…The probe pTA794 contains a 410-bp BamHI fragment including an intergenic spacer and is part of the 5S rDNA gene family isolated from wheat (Gerlach and Dyer 1980). The HT100.3 telomere repeat (TTTAGGG) n sequences were originally isolated and amplified from Arabidopsis thaliana L. (Juchimiuk-Kwasniewska et al 2011). The pAl1 178 bp tandem repeat was cloned from Arabidopsis thaliana L. (Martinez-Zapater et al 1986).…”
mentioning
confidence: 99%